Quality and its Measurement in Transportation, Infocommunication and Postal Services - Hrnciar, Miroslav (Communications - Scientific letters of the University of Zilina, 2002)
Transportation, Info-Communication and Postal Services (TICPS) have a special position in the sector of services when taking into consideration the organization and management of processes. The paper describes the common features of services from the quality management point of view and compares the common used criteria in selected types of services. In the paper, the basic approaches to quality measurement in TICPS from customer and organisational points of view are presented as well. The paper is based on the solution and the conclusions of research project 519/2 “The model of a communication service within a territory administration – region”.